Microlinguistic and macrolinguistic approaches to qur'anic learning - Rohman, Abdul (Islamic perspective on Communication and Psychology, 2024)
Background: Qur'anic learning often focuses on the aspects of memorization and literal understanding of the text, without considering linguistic approaches that can enrich interpretation and understanding. This study aims to explore the application of linguistic approaches in Qur'anic learning to improve understanding and interpretation of Qur'anic verses. Methods: The approach used in this study is qualitative analysis by utilizing linguistic theories such as syntax, semantics, sociolinguistics, psycholinguistics, anthropolinguistics, and ecolinguistics. Data were collected through an in-depth literature review on the application of linguistic approaches in Qur'anic learning, as well as case studies illustrating linguistic-based learning practices. Findings: This study found that the application of linguistic approaches in Qur'anic learning can improve understanding of language structure, verse meaning, and the social and cultural context contained in the text. Syntactic and semantic aspects help readers understand the word order and meaning of verses, while sociolinguistic aspects provide insight into the role of language in social and cultural contexts. Conclusion: The application of the linguistic approach in Qur'anic learning contributes significantly to deepening the understanding of the Qur'anic text. This approach allows readers to not only understand the meaning of words, but also capture the broader meaning of Qur'ānic verses, which relates to social, cultural and psychological contexts. Novelty/Originality of this article: This article contributes by integrating various branches of linguistics, including syntax, semantics, sociolinguistics, psycholinguistics, anthropolinguistics, and ecolinguistics, in the context of Qur'anic learning, which has rarely been the main focus in previous studies. This opens up new perspectives in Qur'anic learning methods that are more comprehensive and applicable.